MECHANICAL AND MICROSTRUCTURAL CHARACTERIZATION OF HEAT TREATED A-283C LOW CARBON STEEL - Njoku, Christian Onyewuchi; Gambo, Anthony Victor; Donatus, Rexcharles Enyinna (FUDMA JOURNAL OF SCIENCES, 2025)
The research is aimed at investigating the impact of heat treatment on the mechanical and microstructural characteristics of A-283C low carbon steel and its performance under different conditions of cooling. The combined effect of metallurgical microscopy for surface examination with mechanical testing such as Tensile Strength, Hardness, Yield Strength, Young Modulus, Percentage Elongation, and Percentage Reduction were analyzed. The findings posit that applying particular heat treatments for a given application in a given field greatly enhanced the mechanical properties of the mild steel. The outcomes of investigation showed that yield strength, tensile strength, and hardness of A-283C steel increased with plastic deformation while percentage reduction and elongation decreased due to strain hardening effect.